Bias Psikologis Mahasiswa Generasi Z Muslim dalam Keputusan Investasi Cryptocurrency - Achmad Roziqin; Khairunnisa Musari (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2026)
Advances in financial technology have driven the increasing involvement of generation Z in investing in crypto assets, which are characterized by high risk and volatility. This study examines how decisions among generation Z muslim students in cryptocurrency investment can be influenced by mental accounting, familiarity bias, and self-attribution bias. The approach used in this study was quantitative with a causal-associative design and a purposive sampling technique on an infinite population of students from the Faculty of Islamic Economics and Business at Kiai Haji Achmad Siddiq Islamic University of Jember. Data collection was conducted through a digital questionnaire, resulting in 32 respondents. These were then analyzed using multiple linear regression, after going through validity, reliability, and classical assumption tests to ensure model feasibility. To confirm and develop the investigation into the results of the answers and the results of data processing, this study continued the saturation interview technique with respondents. This study generated a model contribution of 71.3%, with all three exogenous (independent) variables statistically, both simultaneously and partially, having a positive significance on cryptocurrency investment decisions, with familiarity bias dominating the influence. Overall, these findings further confirm that psychological bias plays a significant role in the investment decision-making process and further reinforce the notion that Generation Z Muslims possess digital financial literacy and actively participate in modern digital financial instruments.